2018
DOI: 10.3390/antiox7070081
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Polyphenolic Extracts from Quercus Laurina, Quercus Crassifolia, and Quercus Scytophylla Bark

Abstract: The objective of this work was to determine the concentration of total phenols, total flavonoids, hydroxycinnamic acids, and proanthocyanidins present in crude extracts of Quercus laurina, Q. crassifolia, and Q. scytophylla bark. They were extracted by ethanol (90%) maceration and hot water. The antioxidant capacity was determined by the ability to capture OH•, O2•−, ROO•, H2O2, NO•, and HClO. The hot water crude extract of Q. crassifolia was chosen to be concentrated and purified due to its higher extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…The strongest antioxidant activity is recorded for BBE2, where the strongest amount of phenols was recorded. Many bark extracts have been evaluated for their antioxidant capacities, commonly associated to their content of phenolic compounds [28,29,30]. Beech bark contains some of biologically active components, such as catechin, epicatechin, syringic acid, vanillic acid etc., indicating that the antioxidant activity of the extracts can be at least partially ascribed to these bio-components (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The strongest antioxidant activity is recorded for BBE2, where the strongest amount of phenols was recorded. Many bark extracts have been evaluated for their antioxidant capacities, commonly associated to their content of phenolic compounds [28,29,30]. Beech bark contains some of biologically active components, such as catechin, epicatechin, syringic acid, vanillic acid etc., indicating that the antioxidant activity of the extracts can be at least partially ascribed to these bio-components (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, researchers have focused their work on improving the flavonoid recovery methods of some barks, especially when highly lignified barks are wasted from the forestry industry. Recent work has mentioned the extraction of flavonoids from the bark of Pinus radiata [ 24 ], chestnuts species [ 25 ], Caesalpinia ferrea C. [ 26 ], Pinus halepensis [ 27 ], Quercus laurina , Quercus crassifolia , and Quercus scytophylla [ 28 ].…”
Section: Natural Sources Of Flavonoidsmentioning
confidence: 99%
“…The observed differences in the bacteria growth inhibition between QCBe and QCBae can be explained by dissimilarities in terms of their chemical composition. A previous study demonstrated that QCBe had a significantly higher content of total phenols, total flavonoids, and hydroxycinnamic acids than QCBae (Valencia-Avilés et al, 2018). The higher phenol content of the purified extract could influence its higher activity toward a gramnegative bacterium, such as E. coli.…”
Section: New Horizons In Food Researchmentioning
confidence: 96%
“…In a previous work, it was determined that a purified extract from a Mexican oak ( Quercus crassifolia bark, QCBe) was a good source of polyphenols (860.39 ± 5.68 mg GAE/g). Additionally, this extract showed a higher free radical scavenging ability in vitro toward reactive species of biological importance (hydroxyl and peroxyl radical and the superoxide anion) than Oligopin®, a commercial polyphenolic extract widely used in nutraceutical products (Valencia‐Avilés et al., ).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation